1960
DOI: 10.2307/3894892
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Line-Interception, Variable-Plot and Loop Methods as Used to Measure Shrub-Crown Cover

Abstract: Determining the percentage of ground covered by shrubby vegetation is an integral part of range inventory and of range condition and trend studies. Measurement of plant cover is used in making site descriptions and in studying brush control, seeding, and grazing management. A change in plant cover often reflects a change in management practices. No accurate method of measuring plant cover has been devised. In most instances only an estimation of plant cover is made. However, Smith (1944) showed that cover esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0
1

Year Published

1963
1963
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 7 publications
(5 reference statements)
1
22
0
1
Order By: Relevance
“…Image analysis may estimate cover to be lower at high cover values compared to the ocular method, because image analysis may better account for foliar openings than the observers. The observers might see cover more as the gross crown spread without accounting for any foliar openings (Daubenmire 1959;Kinsinger et al 1960).…”
Section: Resultsmentioning
confidence: 99%
“…Image analysis may estimate cover to be lower at high cover values compared to the ocular method, because image analysis may better account for foliar openings than the observers. The observers might see cover more as the gross crown spread without accounting for any foliar openings (Daubenmire 1959;Kinsinger et al 1960).…”
Section: Resultsmentioning
confidence: 99%
“…K Dividing equation ( 11) by (12) and simplifying gives the relative amount by which variable plot sampling overestimates the ground cover of elliptical shrubs : E = 1 + b2 (13 2b ) To compute the actual ground cover on the plots used in their comparison of methods, Kinsinger et al ( 1960) measured the long and short axis of every shrub and calculated its area from the ellipse formula. From field data supplied by Kinsinger (personal communication) I have computed the ratio of minor to major axes of the shrubs on each of three plots (Table II).…”
Section: Precautions and Errors In Variable Plot Sampljncmentioning
confidence: 99%
“…

In the incessant search for new and simpler techniques of vegetation analysis, truly original ideas are rare. It seems appropriate to designate it the cm.>er percentage fa.ctor, analogous to the basal area factor used in plotless timber cruising.Tr:STS OF VARIABLE PLOT SAMPLING Comparison of line intercept, variable plot, and loop estimates with true coverage in the open desert shrub vegetation of Nevada showed that line intercept came closest to the value obtained from measurements of every shrub (Kinsinger, Eckert, and Currie 1960). Proposed for estimating tree basal area, it has been adapted to determination of timber volume, and is now widely used in routine forest inventory.

…”
mentioning
confidence: 99%
See 2 more Smart Citations